Deliberate self-harm in a patient with hyperthyroidism with acute psychosis - Haw Huo Wong; Pang, Nicholas Tze Ping (S. Karger AG, 2021)
A woman in her 30s with underlying Graves’ disease, who recently completed radioactive iodine treatment, presented with 2 weeks of acutely altered behaviour associated with auditory hallucinations and religious preoccupations. Laboratory investigation demonstrated elevated free thyroxine levels and suppressed thyroid-stimulating hormone levels. Additionally, there was a presence of antithyroid peroxidase antibodies consistent with autoimmune thyroid disease. She responded to antipsychotics and achieved biochemical euthyroidism. Subsequently, antipsychotic was tapered off during outpatient follow-up at the patient’s own request, with supplement thyroxine continuing. After 1 week, acute hallucinations and religious preoccupations re-emerged, driving her to inflict self-injuries by swallowing coins and nails and banging her head against the wall, sustaining laceration wounds. Furthermore, she hammered a roofing nail into the external genitalia, embedded in the symphysis pubis. After supplemental thyroxine was stopped and olanzapine was started, she achieved biochemical euthyroid followed by remission of psychosis within 1 week. This case illustrates the importance of elucidating organic causes of psychosis as they are easily and swiftly reversible.